Do Intellectual Capital and Financial Performance Connect With Stock Price Volatility? - Haidar Baqir Hidayat; Prasojo Prasojo (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2023)
Purpose: This study aims to analyze the effect of intellectual capital (IC) and financial performance on stock price volatility Methodology: The methodology used is a quantitative approach with panel data regression analysis. The sample selection method used a purposive sampling method with criteria set by the researchers resulting in 37 mining companies from 2014 - 2021. Findings: The results of this study indicate that human capital, structural capital, and capital employed do not affect stock price volatility. Relational capital has a significant positive effect on stock price volatility. Furthermore, earnings volatility and return on assets show a significant positive effect on stock price volatility. The results of this study reject the assumptions of the resource-based view theory. This study has implications for practices in the capital market, where most investors have yet to consider IC in their investment decisions. Novelty: Not much research has been done on the renewal of stock price volatility; The intellectual capital factor uses the Value-Added Intellectual Capital (VAIC) method in the form of human capital, structural capital, employed capital and rational capital; The financial performance factors used are earning volatility, dividend payout ratio and return on assets; Renewal of research objects using mining sector companies; Research data from 2016-2021.